ANALISIS KELAYAKAN BEP DAN TITIK IMPAS USAHA BUDIDAYA PEMBESARAN IKAN GURAMI (Osphronemus gouramy) DI KECAMATAN BANDAR SRIBHAWONO - Bayu Firmansyah; Novia Ambar Sari (Jurnal TROFISH, 2023)
Gourami is a type of freshwater fish native to Indonesia that has been cultivated for a long time. Bandar Sribhawono Village is a village whose people cultivate gourami. This gourami farming is able to move the wheels of the economy in Bandar Sribhawono Village. Therefore, it is necessary to analyze the feasibility of the business and the break-even point of the gourami enlargement business. The purpose of the study was to identify the availability of land, capital, seeds and feed for gourami cultivation businesses in intensive ponds and to determine the level of business profit. This research was conducted in Bandar Sribhawono Village. The research method uses the Descriptive Quantitative method. To calculate the business feasibility analysis using the Gross Benefit Cost ratio (Gross B/C and Break Event Points (BEP). The results of the study showed that the availability of land, capital, seeds and feed for gourami farming businesses in intensive ponds was available in the research area. Based on the feasibility analysis of the gourami enlargement cultivation business, it was declared feasible to be developed because the production volume of Gross B/C > 1 and for ducks breakeven BEP Rupiah showed a revenue of Rp 126,072,200 while farmers' income reached 133,960,000, for the breakeven point BEP production showed a yield of 3,501 kg while the production produced reached 3,940 kg. Keywords: Business Analysis, Gourami. BEP, break-even point